Dynamics of Human Immunodeficiency Virus (HIV)/ Acquired Immune Deficiency Syndrome (AIDS) Cases in Provinsi Sumatra Selatan : Descriptive Study 2021-2023 - Damayanti, Rosa; Hisani, Tarasari; Parakasi, Seriva Raina Parakasi; Sukmadewi, Susi Sukmadewi; balqis, salsabila fadilah (Journal of Epidemiology and Health Science, 2026)
Background: Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) is one of the major global health issues, with prevalence rates that indicate a decline in several countries, including Indonesia. The number of cases of HIV/AIDS in the Province of Sumatera Selatan is quite high from 2021 to 2023. Objective: The purpose of this study is to describe the HIV/AIDS distribution pattern in the Province of Sumatera Selatan, analyze the primary contributing factors, and assess the effectiveness of the countermeasures efforts that have been carried out by the relevant parties. Method: This study uses a quantitative deskriptif approach with secondary data analysis derived from the Profile Kesehatan Provinsi Sumatera Selatan document. The variables under analysis include the number of cases of HIV/AIDS, the distribution of cases according to the type of case, and the number of affected individuals. Results: The analysis's findings indicate that the number of HIV cases has significantly increased, rising from 321 cases in 2021 to 846 cases in 2023. Proportion of sufferers was dominated by man, accounting for 82% of all cases of HIV and 83% of all cases of AIDS. The age group of 20–29 years old has the highest number of HIV-related cases, while the age group of 30–39 years old has the highest number of AIDS-related cases. Conclusion: This highlights the need for health education, access to health services, and stigma reduction for HIV/AIDS patients. It is anticipated that the results of this study will serve as a guide for the local government in determining more appropriate and effective measures to combat HIV/AIDS in the Province of Sumatera Selatan. Keywords: HIV/AIDS,Sumatera Selatan, cases distribution, public health, and countermeasures strategy